2022
DOI: 10.1021/acs.macromol.2c00936
|View full text |Cite
|
Sign up to set email alerts
|

PET-RAFT Enables Efficient and Automated Multiblock Star Synthesis

Abstract: We show that photoinitiated electron/energy transfer–reversible addition–fragmentation chain transfer (PET-RAFT) enables vastly superior control over the polymerization of multiblock star copolymers compared to conventional techniques. Monomodal distributions with dispersities <1.3 could be achieved after the 10th block despite pushing the polymerization to >95% conversion in each block extension. The improvement in control is likely due to the reabsorption of the free radical at the propagating chain end by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 41 publications
0
21
0
Order By: Relevance
“…Further, a recent study has reported the differences between photochemical and the traditional thermal RAFT polymerization using block polymers, indicating superior livingness for the photochemical approach. In 2022, Foster et al showed a similar conclusion, demonstrating the superior control of PET-RAFT compared to conventional RAFT using multiblock star polymers …”
mentioning
confidence: 82%
See 1 more Smart Citation
“…Further, a recent study has reported the differences between photochemical and the traditional thermal RAFT polymerization using block polymers, indicating superior livingness for the photochemical approach. In 2022, Foster et al showed a similar conclusion, demonstrating the superior control of PET-RAFT compared to conventional RAFT using multiblock star polymers …”
mentioning
confidence: 82%
“…In 2022, Foster et al showed a similar conclusion, demonstrating the superior control of PET-RAFT compared to conventional RAFT using multiblock star polymers. 12 Initially, photochemically driven RAFT polymerization has been achieved through the UV-based photolysis of CTAs through the photoiniferter process. 13−16 However, due to the harsh conditions and potential degradation of the CTA, highenergy UV light-irradiated systems can be challenging to implement.…”
mentioning
confidence: 99%
“…279 Finally, Chapman and coworkers analyzed the effects of the type of monomers (hydrophobic, hydrophilic, and charged) and their order of arrangements on the sizes and assemblies of multiblock star polymers in solution. 277 It is noted that the core of star polymers can be linked to either the R or Z group of the CTA (Scheme 23). In the Z-group approach, the polymers grow from the fragmented R group liberated from the core, whereas in the R-group approach, the polymers grow from the core.…”
Section: Single Unit Monomer Insertion (Sumi)mentioning
confidence: 99%
“…279 Finally, Chapman and coworkers analyzed the effects of the type of monomers (hydrophobic, hydrophilic, and charged) and their order of arrangements on the sizes and assemblies of multiblock star polymers in solution. 277…”
Section: Pet-raft Polymerizationmentioning
confidence: 99%
See 1 more Smart Citation